Simplify and then evaluate the equation when x=-3 and y=-1
![Simplify and then evaluate the equation when x3 and y1 class=](https://us-static.z-dn.net/files/d07/4de00f11521677ecc8b76ac433954c55.png)
Hello
We have a given equation and defined variables. All we need to do is substitute the values into the equation and solve.
[tex]\begin{gathered} 2y^2+4(x+2y)+y \\ x=-3 \\ y=-1 \end{gathered}[/tex]Let's substitute the values in and solve
[tex]\begin{gathered} 2y^2+4(x+2y)+y_{} \\ x=-3 \\ y=-1 \\ 2(-1)^2+4(-3+2(-1))+(-1) \\ 2(1)+4(-3-2)-1 \\ 2+4(-5)-1 \\ 2+(-20)-1 \\ 2-20-1=-19 \end{gathered}[/tex]From the calculation above, the value of the equation is equal to -19